Development Program for Culturally Betel Nut Chewing Into A Healthy Behavior of Chewing Through Empowerment of Posyandu Cadres at Puskesmas Tiga Panah Karo Regency - Pintauli, Sondang; Situmorang, Hamzon; Nainggolan, Marline (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The habit of chewing betel nut has a long history of use. Betel nut are widely used among various communities and in several countries across the world. In Indonesia, betel-quid chewing is socially accepted habit that is integrated into both cultural (ceremonial situations) and routine aspects of daily life. Many people chew betel nut for the energy boost it produces. It may also result in feelings of euphoria and well-being. However, most of betel chewers don’t know that there is a relationship between betel nut and various oral lesion in the mouth. Betel nut chewing is implicated in oral submucous fibrosis (OSF) and its use along with tobacco can cause leukoplakia, both of which are potentially malignant in the oral cavity. Public health programs regarding the harmful effects of betel nuts, coupled with increased awareness by healthcare professionals of the signs and symptoms of this disease, can limit its prevalence significantly. Puskesmas Tiga Panah, as one of the primary health centre in Karo regency has potential role to empower Posyandu cadres in approaching people especially the chewers to educating them about the health risks of betel nut use, therefore, the culturally habit of betel chewing would be change into healthy behavior of chewing.